Effects of Cefuroxime and Varying Nitrogen Conditions on Growth and Pigment Composition of Chlorella sp. - Kalaboms Andrew Bitrus Bebwa; Daniel Biyenta Elijah; Yerima Doka Dacip (Darul Yasin Al Sys, 2025)
This study addresses the limited research on the ecological impacts of cefuroxime on freshwater microalgae, despite the antibiotic’s widespread presence in aquatic environments. Specifically, it investigates the effects of cefuroxime on the growth and pigment composition, measured through cell density, chlorophyll-a, chlorophyll-b, total chlorophyll, and carotenoids of Chlorella sp. under nitrogen-replete and nitrogen-limited conditions. A quantitative experimental design was applied, comprising five treatment groups cultured in triplicate. Data collection involved microscopic cell counts and spectrophotometric analysis, while growth and pigment dynamics were assessed using specific growth rate equations and pigment concentration formulas. Statistical analyses included the Shapiro-Wilk test, Levene’s test, repeated measures ANOVA, and Duncan’s Multiple Range Test (p ≤ 0.05). Results indicated that cefuroxime initially stimulated growth and pigment production under nitrogen-replete conditions but led to significant inhibition over time. Conversely, the control group demonstrated the most stable growth and pigment accumulation by day seven. These outcomes challenge the notion that low-dose antibiotics are ecologically benign and underscore the critical role of nitrogen availability in modulating antibiotic effects. The study concludes that cefuroxime exerts time- and nutrient-dependent impacts on Chlorella sp., advancing ecotoxicological theory by elucidating the interactive effects of nutrient stress and pharmaceutical contamination. Practical implications highlight the necessity for stricter regulation of pharmaceutical effluents and improved nutrient management in aquatic systems. Future investigations are recommended to explore the combined effects of multiple antibiotics under varied nutrient regimes.